2008
DOI: 10.1007/s00198-008-0777-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spinal kyphosis on gastroesophageal reflux disease symptoms in patients with osteoporosis

Abstract: Increases in angle of lumbar kyphosis and number of lumbar vertebral fractures may represent very important risk factors for GERD in osteoporotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 38 publications
1
46
0
2
Order By: Relevance
“…With regard to the digestive organs, several studies have pointed out that inflammatory bowel disease1113 and gastrectomy14 are related to development of osteoporosis. In more recent years, Helicobacter pylori infection,1520 hiatal hernia,21 reflux esophagitis,2224 gastric mucosal atrophy,25 and proton pump inhibitor (PPI) use26,27 have also been identified as possible risk factors for osteoporosis. However, there are few reports about these as risk factors for asymptomatic osteoporosis based on multivariate analysis in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the digestive organs, several studies have pointed out that inflammatory bowel disease1113 and gastrectomy14 are related to development of osteoporosis. In more recent years, Helicobacter pylori infection,1520 hiatal hernia,21 reflux esophagitis,2224 gastric mucosal atrophy,25 and proton pump inhibitor (PPI) use26,27 have also been identified as possible risk factors for osteoporosis. However, there are few reports about these as risk factors for asymptomatic osteoporosis based on multivariate analysis in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…It was interesting that in our study there was a male preponderance in the LSBE group compared to the proportion of males in the SSBE group. In Japan, kyphosis is more prevalent in female patients than in males (6,(21)(22)(23). Only 27% of the patients with LSBE were female in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Some investigators have reported that an increased Cobb angle induced by numerous fractures of the lumbar vertebrae may be important risk factors for gastroesophageal reflux disease in patients with osteoporosis (20,21). Yoshimura et al also reported that the presence of vertebral fractures is significantly associated with the presence of either erosive esophagitis or hiatal hernia (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported a correlation between GERD and kyphosis. 11,12 According to a literature review by Fujiwara and Arakawa, 13 the estimated prevalence of GERD in a whole Japanese population ranged from 6.6% to 37.6%, which is variable; however, another study found that approximately 24% of patients with kyphosis had GERD. 12 Similar to these previous studies, the prevalence of GERD in the kyphosis group and in the control group in our study were 35% and 9.8%, respectively.…”
Section: Article In Pressmentioning
confidence: 98%